The Urgency of Tolerance-Based Education: Integration of Religious Moderation and Social Science - Futri Syam; Sahyul Pahmi (Universitas Teuku Umar, 2022)
In this era of globalization, the integration of religious moderation in education has an important role in maintaining inter-religious harmony. Social Studies can be an effective platform to introduce the concept of religious moderation to students. This study uses a qualitative research approach with an interview method to explore educators' strategies in integrating social studies learning and religious moderation. The results of the analysis show that the integration of religious moderation in social studies has several significant benefits. First, this approach allows learners to gain a better understanding of the religions around them, respect differences, and avoid prejudice or negative stereotypes. Second, the integration of religious moderation can facilitate interfaith dialog and build trust among learners with different religious backgrounds. Third, it encourages learners to develop an attitude of tolerance and mutual respect in building an inclusive and harmonious society. However, this study also identified some challenges faced in implementing the integration of religious moderation in social studies subjects. Some of these challenges include diverse perspectives on religious moderation, limited availability of resources, and educators' ability to manage and facilitate sensitive discussions about religion. This research contributes to the understanding of the effectiveness of religious moderation integration in social studies learning. The results of this study can be used by educators and policy makers to improve and develop religious moderation integration programs in the education curriculum.